2018
DOI: 10.1038/s41390-018-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for reticulocyte hemoglobin content in healthy infants

Abstract: This longitudinal study presents Ret-He reference intervals based on non-anemic and non-iron-deficient infants and constitutes a step towards standardizing Ret-He as a pre-anemia biomarker of iron deficiency in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
4
15
0
1
Order By: Relevance
“…9,10 Conventional iron biomarkers are also affected by acute-phase responses, 8,12 and influenced by diurnal variation and dietary intake. 12,13 Due to these diagnostic difficulties, an alternative marker is sought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Conventional iron biomarkers are also affected by acute-phase responses, 8,12 and influenced by diurnal variation and dietary intake. 12,13 Due to these diagnostic difficulties, an alternative marker is sought.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow iron staining, the gold standard method for diagnosing iron deficiency, is invasive [8][9][10][11] and subjective. 9,10 Conventional iron biomarkers are also affected by acute-phase responses, 8,12 and influenced by diurnal variation and dietary intake. 12,13 Due to these diagnostic difficulties, an alternative marker is sought.…”
Section: Introductionmentioning
confidence: 99%
“…In term newborns, mean hemoglobin values decreased approximately 5 g/dL between birth and 28 days of life and the mean platelet count increased 140 3 10 3 /lL by 90 days of life. 17 Lofving et al 21 reported that RET-He decreases after birth and levels off at 4 months. Neutrophil counts are low at delivery, but increase after birth, with a peak value between 6 and 14 HOL, then decreasing and leveling off at approximately 72 hours.…”
Section: Discussion Factors That Can Affect Cbc Reference Intervalsmentioning
confidence: 99%
“…17 Broad reference interval widths do have implications in clinical practice as these may reduce diagnostic power and even small to modest overestimation may result in higher false negative rates. 33 Of note is that reference intervals specifically for Ret-He, using data from the County Hospital of Halland cohort, have already been previously published, 28 but with different reference interval methodology (a parametric approach). Since these calculations are less robust to population skewness, we did further analyses and harmonised calculations with the other RBC biomarkers.…”
Section: Original Researchmentioning
confidence: 99%